THE INFLUENCE OF THE USE OF SIPOLAN ICONS AS SOCIAL MEDIA CONTENT IN INFORMATION DISSEMINATION PROGRAMS (CASE STUDY AT THE CLASS I IMMIGRATION OFFICE OF TPI POLONIA) - R.S Akbar; I.A Prabadhi; A.M.S Simamora (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2022)
This SIPOLAN was created with the aim of providing an immigration image with a Mido midi design wrapped in the Batak Toba custom with ulos and sortal which depicts the location of the Polonia immigration office in North Sumatra. The pattern used in graphic designs and graphic videos are shows in every post of the Polonia Immigration Office on various platforms. This study used associative quantitative causal relationship to measure how far SIPOLAN's social media content influences the effectiveness of immigration information dissemination by Polonia Immigration Office information section is published on the platform used by the office. This research can be used as input for the TIKIM Subdivision (Immigration Information and Communication Technology). At the Polonia Immigration Office, so that content on social media published by the Polonia Immigration Office has more effective standardization in delivery and delivery strategies to the public, the use of SIPOLAN Social Media Content has an effect of 87.7% on the ease of dissemination information and residue due to the influence of other factors 12.3% which were not applied in this study in the form of interactions from outside social media or face-to-face employees with each other, with superiors or with the public.,